The Method of Averaged Quality Traits in the Management of the Quality of Marketing Information - Joanna MAJCHRZAK (Communications of International Proceedings, 2020)
The paper considers the problem of studying and assessing the quality of the company's marketing information. The main objective of the research is to adjust and apply the method of quantifying quality, i.e., the method of averaged quality traits, to compute the indicator of marketing information quality. In the research into the quality of marketing information, a selective model of information processing was adopted. Referring to the basics of marketing management, i.e., the marketing mix model and the structure of marketing relationships, the distinguishing features of marketing information are presented. Selected concepts of information quality were considered and the quality of marketing information was determined. The essence of the applied method of quantifying quality and the essence of calculating and interpreting the value of the quality indicator, J, was explained. The concept of using the averaged quality traits method in assessing the quality of marketing information was developed. The quality of marketing information is assessed by the value of individual states of features belonging to marketing information. The developed method was used in the study and it evaluates the quality of marketing information of industrial enterprises. The results show the effectiveness of the method in terms of calculating the value of the marketing information quality indicator and the classification of information into individual quality classes. The obtained results are important at the stage of planning the quality of marketing information, i.e., studying, analyzing and designing qualitative changes in managing the quality of marketing information.
Keywords: Quality Management; Qualitology; Information Quality; Marketing.